A Century in the International Community: International Law and Lithuanian Statehood - Satkauskas, Rytis (Teisė, 2022)
One hundred years ago Lithuania became a member of the League of Nations. The membership was based on the perceived advantages of the international system and the importance of the rule of law to the region. The vision of global peace based on the prohibition of aggression and law enabled Lithuania to establish statehood. Conditions for the recognition of the new member of international community ranged from the requirement of established borders and a democratic government to guarantees regarding commitment to protect national minorities and control armaments. The research confirms that the implementation of these commitments was understood in Lithuania not only as a condition for membership but as an important direct objective. The Lithuanian political elite had no illusions as to the importance of international law in disputes with neighbouring states. A good-willed implementation of the existing rules was certainly the best defense against the political pressure of military superpowers. This research into the geopolitical situation at the end of WWI and the political discourse in the newly independent Lithuania illustrates the importance of the institutionalized system of nations in ensuring world peace and security.